Development of spinal fusion system - Foo, Mee Lim. (2008)
The objectives of this project are to design a new interbody fusion device with special features, such as variable height to accommodate varying intervertebral disk heights and sharp edges that “lock” in in the vertebrae to provide better stability. Also, compression and fatigue tests were conducted to evaluate its ability to withstand actual loading conditions within the human body.